2016
DOI: 10.1177/1533034615625519
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Relationship Between Aldosterone Synthase CYP1A1 MspI Gene Polymorphism and Prostate Cancer Risk

Abstract: After investigating the peer-review process for the article, SAGE and Editor have determined that the submitting author supplied fabricated contact details for legitimate individuals named as recommended reviewers for the articles. The Editor accepted the paper based on the peer-review comments submitted from the discredited e-mail accounts. SAGE and the Editor apologize to readers and regret that the academic record has been compromised as a result of this manipulation of the peerreview process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In liver cancer cells, over-expression of CYP1A1 induced by plant natural products has been associated with Aryl-hydrocarbon Receptor transformation [36,37]. Furthermore, as a steroid-metabolizing enzyme, CYP1A1 is part of cancer metabolic processes relevant to steroid hormone responsive tumors, such as breast cancer, ovarian cancer, and prostate cancer [38][39][40][41]. Therefore, CYP1A1 may be of particular interest in understanding the mechanism of action of CKI on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In liver cancer cells, over-expression of CYP1A1 induced by plant natural products has been associated with Aryl-hydrocarbon Receptor transformation [36,37]. Furthermore, as a steroid-metabolizing enzyme, CYP1A1 is part of cancer metabolic processes relevant to steroid hormone responsive tumors, such as breast cancer, ovarian cancer, and prostate cancer [38][39][40][41]. Therefore, CYP1A1 may be of particular interest in understanding the mechanism of action of CKI on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies and also the recent meta-analyses showed the association between these SNVs and PCa risk [84][85][86].…”
Section: Carcinogen Metabolismmentioning
confidence: 96%